Inference of local invasion pathways in two invasive crayfish species displaying contrasting genetic patterns. Issue 12 (21st September 2021) - Paz‐Vinas, Ivan; Lang, Iris; Millet, Paul; Veyssière, Charlotte; Loot, Géraldine; Cucherousset, Julien
Abstract: The efficient management of invasive alien species (IAS) requires the identification of their introduction pathways. Genetic assessments have proven useful to inform invasion pathways at large (national to worldwide) scales, but studies at local scales are still rare, despite their importance for guiding management. In this study, genetic analyses were used to identify local invasion pathways of two invasive crayfish species (the spiny‐cheek crayfish Faxonius limosus and the red swamp crayfish Procambarus clarkii ) in a dense network of artificial lakes. We first characterized the spatial patterns of genetic variability, effective population sizes ( Ne ) and among‐lakes recent migration events for each species using neutral microsatellite markers. We then identified the environmental factors affecting genetic variability and inferred the potential local invasion pathways. Results revealed different patterns of genetic variability between the two species: F . limosus displayed very low levels of genetic diversity, Ne and spatial structuring compared to P. clarkii, which displayed high genetic diversity, Ne and spatial genetic structuring. We also demonstrated context‐dependent effects of different environmental factors (fishery management, spatial distribution and lake size) on genetic variability indices. We did not identify local invasion pathways for F. limosus due to limited genetic variability, likely caused by a strong founder effect and potential parthenogenetic reproduction. Contrastingly, multiple invasion pathways (release, contaminant, unaided/corridor spread and stowaway) were identified for P. clarkii . Synthesis and applications . Although limited in some particular cases (e.g. for species having experienced strong shaping events and/or displaying asexual reproductive modes), neutral genetic variation assessments can provide important insights for inferring local invasion pathways in complex landscapes for invasive alien species displaying short generation times and complex invasion histories. Abstract : Although limited in some particular cases (e.g. for species having experienced strong shaping events and/or displaying asexual reproductive modes), neutral genetic variation assessments can provide important insights for inferring local invasion pathways in complex landscapes for invasive alien species displaying short generation times and complex invasion histories. Résumé: Identifier les vecteurs d'introduction des espèces exotiques envahissantes (EEE) est nécessaire pour leur gestion. Les études génétiques se sont avérées très utiles pour identifier ces vecteurs à larges échelles (échelles nationales à mondiales), mais les analyses à des échelles plus locales restent rares, malgré leur importance pour aider à la gestion des EEE. Dans cette étude, nous avons utilisé des analyses génétiques pour identifier les vecteurs d'introduction utilisés, à l'échelle locale, par deux espèces d'écrevisses invasives (l'écrevisse américaine Faxonius limosus et l'écrevisse de Louisiane Procambarus clarkii ) dans un réseau dense de lacs artificiels. À l'aide de marqueurs microsatellites neutres, nous avons d'abord caractérisé les patrons spatiaux de variabilité génétique des deux espèces, les tailles efficaces de leurs populations ( Ne ) et les événements de migration récents ayant eu lieu entre lacs. Nous avons ensuite identifié les facteurs environnementaux influençant la variabilité génétique pour en déduire les vecteurs d'introduction potentiels de ces deux espèces. Nous avons trouvé des patrons de variabilité génétique différents entre les deux espèces : les populations de F. limosus se caractérisaient par de très faibles niveaux de diversité génétique, des Ne faibles et par une faible structuration spatiale par rapport à P. clarkii, espèce pour laquelle les populations se caractérisaient par des diversités génétiques élevées, des Ne forts et par une forte structuration génétique spatiale. Nous avons également détecté des effets contexte‐dépendants de divers facteurs environnementaux (à savoir, intensité de la gestion halieutique, distribution spatiale et taille des lacs) sur les indices de variabilité génétique. Nous n'avons pas pu identifier des vecteurs d'introduction clairs à l'échelle locale pour F. limosus, en raison notamment de sa variabilité génétique très limitée, certainement causée par un fort effet fondateur et une reproduction potentiellement parthénogénétique. Au contraire, de multiples vecteurs d'invasion (introductions volontaires, en tant que contaminant ou en tant que passager clandestin, propagation sans aide ou en suivant un corridor d'origine anthropique) ont été identifiées pour P. clarkii . Synthèse et applications . bien que limitée dans certains cas particuliers (forts événements démographiques, modes de reproduction asexués), l'étude de la variation génétique neutre peut fournir des informations importantes pour identifier les vecteurs d'introduction à des échelles locales, notamment dans des paysages complexes et chez des espèces exotiques envahissantes ayant des temps de génération courts et des histoires d'invasion complexes.